Research on the dissemination of celebrities’ opinions based on speech act theory and potential category analysis - Li, Xinhe; Ju, Chunhua; Li, Ke; Wang, Chenyu; Li, Chuang; Yu, Jie (Frontiers in Psychology, 2022)
With the increasingly prominent role of social media in the timeliness and sharing of information dissemination, more and more research has focused on how to further improve user stickiness through social media. However, there is little consideration of the impact of celebrities’ views on user behavior in social media. The main goal of this paper is to study the influence of celebrity language style on user communication and opinions dissemination. Firstly, it analyzes the language style characteristics of celebrities’ opinions, and conducts cross-influence analysis between celebrity language style characteristics and user communication characteristics. Based on speech act theory, this paper studies the influence of different language styles of celebrity Weibo on users’ communication behavior, and then builds a potential category analysis model to subdivide the views of celebrities. The results show that: 1) Positive expression is the most common language style element combination of celebrities, and it also shows the most effective communication effect. This shows that users like to see celebrities show an active and positive side to the outside world, can analyze external things, and express their own opinions on these contents; 2) The combination of positive emotion, external attention, and analysis can produce the best communication effect; 3) The emotion of celebrities’ opinions will affect the communication emotion of users to a certain extent, and the communication of users will have the development trend of reducing positive emotions and increasing negative emotions. Therefore, positive guidance and the dissemination of positive energy are more needed on public social platforms to minimize or avoid the dissemination of negative emotions.